Clinical profile of cutaneous manifestations of connective tissue diseases in North-East India - Subba, Deepa Mala; Thokchom, Nandakishore; Kongbam, Linda; Salam, Erika; Yumnam, Deepa (International Journal of Research in Dermatology, 2021)
Background: Connective tissue diseases (CTDs) are a heterogeneous group of autoimmune disorders having overlapping clinical features. Skin is often involved and it may be the earliest sign of the disease. This study highlighted the various cutaneous manifestations of common CTDs. Methods: A hospital-based cross-sectional study was carried out for a period of two years in 83 patients with CTDs in dermatology OPD, RIMS, Imphal. Detailed history taking, examination and relevant serological tests were performed. Results: The mean age was 39.78±17.29 years with female to male ratio of 4.5:1. Majority of the patients had lupus erythematosus (LE) (N=45) followed by systemic sclerosis (SSc) (N=25), rheumatoid arthritis (RA) (N=6), mixed connective tissue disease (MCTD) (N=4) and morphea (N=3). The most common presentation was raised skin lesions (45.8%) followed by Raynaud’s phenomenon (36.1%), photosensitivity (27.7%), skin tightness (26.5%) and joint pain (19.3%). Among LE patients, chronic cutaneous lupus erythematosus (CCLE) was the commonest variant and localised discoid lupus erythematosus (DLE) (22.9%) was the commonest presentation followed by malar rash and annular subacute lupus erythematosus (SCLE). Skin induration, microstomia and sclerodactyly were seen in most patients of SSc. Antinuclear antibodies were positive in 89.1% of patients. Anti-dsDNA and anti-Sm antibodies were positive in 62.2% and 33.3% of LE patients, anti-Scl 70 antibody was positive in 68% of SSc patients. Conclusions: CTDs are rare but potentially life-threatening. Proper understanding of the spectrum of cutaneous manifestations of CTDs is therefore necessary for early diagnosis and efficient management.